The Potential Link between Thermal Resistance and Virulence in Salmonella: A Review - Dawoud, Turki M.; Davis, Morgan L.; Park, Si Hong; Kim, Sun Ae; Kwon, Young Min; Jarvis, Nathan; O’Bryan, Corliss A.; Shi, Zhaohao; Crandall, Philip G.; Ricke, Steven C. (Frontiers in Veterinary Science, 2017)
In some animals, the typical body temperature can be higher than humans, for example, 42°C in poultry and 40°C in rabbits which can be a potential thermal stress challenge for pathogens. Even in animals with lower body temperatures, when infection occurs, the immune system may increase body temperature to reduce the chance of survival for pathogens. However, some pathogens can still easily overcome higher body temperatures and/or rise in body temperatures through expression of stress response mechanisms. Salmonella is the causative agent of one of the most prevalent foodborne illnesses, salmonellosis, and can readily survive over a wide range of temperatures due to the efficient expression of the heat (thermal) stress response. Therefore, thermal resistance mechanisms can provide cross protection against other stresses including the non-specific host defenses found within the human body thus increasing pathogenic potential. Understanding the molecular mechanisms associated with thermal responses in Salmonella is crucial in designing and developing more effective or new treatments for reducing and eliminating infection caused by Salmonella that have survived heat stress. In this review, Salmonella thermal resistance is assessed followed by an overview of the thermal stress responses with a focus on gene regulation by sigma factors, heat shock proteins, along with the corresponding thermosensors and their association with virulence expression including a focus on a potential link between heat resistance and potential for infection.